2009
DOI: 10.1097/mao.0b013e31819a8df6
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for the Conservative Management of Vestibular Schwannomas

Abstract: Growth is usually manifest in the first 3 years after presentation. We recommend an initial magnetic resonance imaging scan at 6 months, with scans to take place at annual intervals for 2 years. A further scan 2 years later will identify any patient with indolent tumors. Thereafter, follow-up should be lifelong every 5 years. Cystic tumors represent a particular threat to patients and should only be treated conservatively with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 13 publications
3
60
0
Order By: Relevance
“…Such screening options included hearing tests, which were reported to be equivocal between lesions that grew and those that did not. 9,17,31 Interestingly, in line with the findings of Nikolopoulos et al, 22 Martin and colleagues 16 also suggested that cystic tumors should be followed more closely, as they represented a disproportionate percentage of the tumors that grew, especially in cases in which a solid tumor converted into a cystic one.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Such screening options included hearing tests, which were reported to be equivocal between lesions that grew and those that did not. 9,17,31 Interestingly, in line with the findings of Nikolopoulos et al, 22 Martin and colleagues 16 also suggested that cystic tumors should be followed more closely, as they represented a disproportionate percentage of the tumors that grew, especially in cases in which a solid tumor converted into a cystic one.…”
supporting
confidence: 65%
“…The protocol established by Martin et al 16 contrasts with the one proposed by Strangerup et al, 32 who suggested annual scans for 5 years after treatment and then follow-up scans at 7, 9, and 14 years after treatment. Smouha et al 29 proposed a different strategy, suggesting that those selected for conservative management should undergo MRI studies at 6 months after treatment and ev-ery year thereafter.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Martin et al 34 analyzed 320 patients who underwent observation after an intracanalicular tumor or a tumor smaller than 2 cm in diameter was found. The mean follow-up was 43 months, and 276 patients had at least 1 follow-up image.…”
Section: Observation: the "Wait And Scan" Optionmentioning
confidence: 99%
“…Wait and scan policy consists of consecutive MRIs for a period of up to 5 years. [8][9][10][11] So far, growth in MRI and clinical symptoms are considered decisive in patient management planning.…”
Section: Introductionmentioning
confidence: 99%